Dampak Pengaruh Teknologi Informasi Dan Komunikasi di Banuh Raya - Dina Revani Saragih; Octa Palentina Saragih; Hartati Rodearna Sitio; Savirgi Badira Amri; Sintong Brido Simanjuntak; Didi Syahputra; Ahmad Tarez Azhdi; Tia Amanda Saragih; Jun Kifran R. Manik; Dian G Purba (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Information Technology is technology used to manipulate data in various ways. For example, this technology can process, access, organize and store data. The aim of using information technology is to produce high quality information. Information and Communication Technology has influenced the way humans communicate, work and live. In the business sector, ICT has helped efficiency in business processes and communication between customers, employees and business partners. In the field of education, ICT has changed the way of teaching and learning, providing access to online educational resources, and opening up opportunities for distance learning as discussed this time regarding the utilization or use of information and communication technology in BANUH RAYA, SIMALUNGUN, which has a population of approximately 150 families where the use of technology in this area is still lacking due to network difficulties where sometimes residents have to climb to higher places to get a network. Information Technology is technology used to manipulate data in various ways. For example, this technology can process, access, organize and store data. The aim of using information technology is to produce high quality information. Information and Communication Technology has influenced the way humans communicate, work and live. In the business sector, ICT has helped efficiency in business processes and communication between customers, employees and business partners. In the field of education, ICT has changed the way of teaching and learning, providing access to online educational resources, and opening up opportunities for distance learning as discussed this time regarding the utilization or use of information and communication technology in BANUH RAYA, SIMALUNGUN, which has a population of approximately 150 families where the use of technology in this area is still lacking due to network difficulties where sometimes residents have to climb to higher places to get a network.